Uterine and umbilical artery doppler in women with pre-eclampsia and their pregnancy outcomes - Adekanmi, Ademola; Roberts, Adebola; Akinmoladun, Janet; Adeyinka, Abiodun (The Nigerian postgraduate medical journal, 2019)
Background: Pre-eclampsia (PE) is an important public health menace in both developed and developing countries with high maternal and perinatal morbidity and mortality globally. A major goal towards improving antenatal management of PE is to develop accurate prediction models that identify women at high risk of this disease for appropriate interventions. Methodology: In a longitudinal cohort study, high-risk singleton pregnant women enroled between April 2015 and February 2016 had uterine and umbilical artery Doppler sonography at 22-24 weeks and 32-34 weeks gestation and had their delivery outcomes documented by the obstetrician and gynaecologist. The peak systolic velocity (PSV), end-diastolic velocity (EDV), Resistivity Index (RI), Pulsatility Index (PI) and the systolic-diastolic ratio (S/D) were recorded. Results: Among the ninety-eight high-risk pregnant women, 61 (62.2%) developed PE and 32 (32.8%) did not have PE. In the PE cases, 15 (24.5%) were mild and 46 (74.5%) were severe PE. The uterine artery PI was significantly associated with PE. A unit increase in uterine PI in high-risk pregnancies, increases the odd of PE by 37.37 times (95% confidence interval; odds ratio = 6.09, 241.9; P < 0.001). The combination of the uterine and umbilical PSV predicted 80.3% of severe PE. All three spontaneous abortions were in women who developed PE, more caesarean section (48.4%) and 69.2% of 45 pre-term deliveries occurred in women with severe PE. Conclusion: The findings from this study show significantly lower uterine and umbilical arteries PSV and EDV but higher RI, PI and S/D in cases that developed PE. The uterine artery PI is the best predictor of PE, whereas the combinations of uterine and umbilical arteries PSV best predict severity of PE among high-risk pregnant Nigeria women.